2017
DOI: 10.1177/1048291117739417
|View full text |Cite
|
Sign up to set email alerts
|

The Job Content, Context, and Requirements of Regulated Home-Based Childcare Workers

Abstract: Contrary to a large and growing literature on center-based childcare workers, we know little about the work and health experiences of those providing childcare services in their homes. This study examines the job content, context, and requirements of regulated Home-Based Childcare workers in Canada. It is based on the qualitative analysis of eleven individual semistructured interviews. These workers perform business administration tasks and more housekeeping and domestic work than those in the center-based chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Inaddition,'fearsoftechnicalfailure'andthesubsequentnegativeimpactonwellbeingreportedly increased with working from home (Daniel et al2018) 16 . Mann et al(2003)25 (qualitativeinterviews)reportedthatteleworkersmayexperienceadecrease instressattributabletotheperceptionofhavingcontrolovertheirwork(environmentandwork schedules).Tietzeet al(2011)33 (interviews and focus groups) reported that working from home made iteasierforparticipantstomanagetheirownworkloadsandconsequentlyaddressequityissuesand experienceimprovedwellbeing.However,Stitouet al(2018)31 (interviews, n=11)reportedthatfactorsrESULTS 40 NIHR Journals Library www.journalslibrary.nihr.ac.uk affectinghealthandwellbeingincludedinterferencewithpersonalandfamilylife.Danielet al(2018)…”
mentioning
confidence: 99%
“…Inaddition,'fearsoftechnicalfailure'andthesubsequentnegativeimpactonwellbeingreportedly increased with working from home (Daniel et al2018) 16 . Mann et al(2003)25 (qualitativeinterviews)reportedthatteleworkersmayexperienceadecrease instressattributabletotheperceptionofhavingcontrolovertheirwork(environmentandwork schedules).Tietzeet al(2011)33 (interviews and focus groups) reported that working from home made iteasierforparticipantstomanagetheirownworkloadsandconsequentlyaddressequityissuesand experienceimprovedwellbeing.However,Stitouet al(2018)31 (interviews, n=11)reportedthatfactorsrESULTS 40 NIHR Journals Library www.journalslibrary.nihr.ac.uk affectinghealthandwellbeingincludedinterferencewithpersonalandfamilylife.Danielet al(2018)…”
mentioning
confidence: 99%
“…Research in the ECEC sector has predominately focused on center-based services ( Tonge et al, 2016 , Wolfenden et al, 2020 ), with less research conducted in home-based child care settings ( Francis et al, 2018 , Yoong et al, 2020 ). Home-based childcare services have distinct challenges compared to center-based services, with one educator often providing education and care for multiple children of different ages and abilities ( Stitou et al, 2018 ). Additional structural barriers in home-based childcare, such as equipment availability, challenges participating in professional development, and limited budget, space and resources, also mean findings from research in center-based services may not be generalizable to home-based childcare services ( Fees et al, 2009 , O’Connor and Temple, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence shows that unfavorable health outcomes among childcare workers could be detrimental to both the workers and the children under their care [4, 5]. A recent Canadian study identified several factors that can potentially affect health outcomes among childcare workers including high physical and mental efforts, exposure to noise and bad odors, and inadequate remuneration [6]. A European study estimated the prevalence of effort-reward imbalance among childcare workers in Germany to be around 65% [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, research has shown that proper management of these issues could lead to better health outcomes for childcare workers, as well as favorable care outcomes (e.g. reduction in injuries) for children [6, 10].…”
Section: Introductionmentioning
confidence: 99%